2015
DOI: 10.5539/jps.v4n2p12
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Influence of Bagging of Fruits at Marble Stage on Quality of Mango cv. Alphonso

Abstract: Preharvest fruit bagging has emerged as a novel technology in practice, which is simple, grower friendly, safe and beneficial for production of quality fruits. An investigation was undertaken in 2013 and 2014 for two consecutive fruiting seasons entitled studies on influence of bagging of fruits at marble stage on quality of mango cv. Alphonso. The fruits were bagged at marble stage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 15 publications
19
13
0
Order By: Relevance
“…The findings revealed that percent total soluble solids increased sharply from harvest to ripe fruits have got support of (Joshi and Roy,1988) who mentioned that TSS increase initially and declined later on. Similar finding was recorded in some previous studies (Haldankar et al, 2015;Awad, 2007;Singh et al, 2007).…”
Section: Total Soluble Solid (% Brix)supporting
confidence: 93%
See 3 more Smart Citations
“…The findings revealed that percent total soluble solids increased sharply from harvest to ripe fruits have got support of (Joshi and Roy,1988) who mentioned that TSS increase initially and declined later on. Similar finding was recorded in some previous studies (Haldankar et al, 2015;Awad, 2007;Singh et al, 2007).…”
Section: Total Soluble Solid (% Brix)supporting
confidence: 93%
“…During ripe stage, the highest reducing sugars were recorded in white paper bag (1.41%) while the lowest was recorded in muslin cloth bags (0.93%) (Table 04). Similar findings were found in some previous research (Haldankar et al, 2015). They reported that fruits of newspaper bag exhibited the maximum reducing sugars at ripe stage in mango and soluble sugar was increased in grape due to pre-harvest bagging treatments.…”
Section: Reducing Sugars (%)supporting
confidence: 91%
See 2 more Smart Citations
“…The practice of pre-harvest bagging has been extensively used in several fruit crops, such as mango [19,20,4,21,3,7,8], apple [22], pear [23,24], peach [25], longan [26], to improve the commercial value of the fruit, namely, improving fruit coloration [27], reducing mechanical damage [28] and sunburn [29] of the skin. Pre-harvest bagging also reduces pesticide in the fruit [28] and improves insect [30], disease [31] and bird damage control [28].…”
Section: Resultsmentioning
confidence: 99%